Superonasal Transconjunctival Optic Nerve Sheath Decompression: A Simplified Technique for Safe and Efficient Decompression. Issue 1 (3rd March 2021) - Melson, Andrew T.; Warmath, Jacob D.; Moreau, Annie; Farris, Bradley K.
Abstract : Background: Severe, permanent vision loss is a feared sequela of untreated or refractory idiopathic intracranial hypertension (IIH). For patients with progressive vision loss despite maximally tolerated medical treatment, optic nerve sheath decompression (ONSD) remains a viable and effective option to protect vision. Our objective is to introduce a modified transconjunctival technique for ONSD and determine its safety, efficacy, and efficiency in patients with IIH. Methods: We performed analyses for a retrospective case series of consecutive patients with IIH by modified dandy criteria who underwent isolated superonasal transconjunctival optic nerve sheath decompression (stOND) at single eye institute in a large academic center from January 2013 to February 2017. Sixty-six patients were identified who met these criteria with at least 6 weeks of follow-up data. Primary outcome measures were visual field mean deviation, grading of papilledema by the modified Frisen scale, and best-corrected visual acuity. Secondary outcome measures were presence of postoperative diplopia and operative time. Results: One hundred thirty-two eyes of 66 patients were identified; 58 were female (88%), and 8 were male (12%). The mean age was 30 years (range 13–55) with an average lumbar puncture opening pressure of 38 cm H2 O. Participants mean body mass index was 36 (range 20–59) with Grade 3 papilledema on average by the modified Frisen scale. No patients experienced operative complications, postoperative diplopia, or worse visual acuity at 1 week after surgery. Average operative time was 50 minutes (range: 25–89). The median decrease in papilledema grading was 3 grades on the Frisen scale (95% confidence interval [CI], 2–3, P < 0.0001). Snellen visual acuity changes did not meet statistical significance. The average Humphrey Visual Field mean deviation change was +1.91 (95% CI, 0.58–3.24, P = 0.0052). Despite successful bilateral decompressions, 4 patients (6.1%) progressed in their visual loss. Conclusions: The superonasal transconjunctival approach to ONSD is a safe, efficient and effective surgical treatment for patients with deteriorating visual function due to IIH. Although additional study is required to further clarify the best timing and indications for ONSD among other treatment options for refractory IIH, providers should be aware of the reduced complication rates and efficacy of the stOND technique.